The role of genes from several different plant defence pathways in resistance to the Fusarium Head Blight causing pathogen, Fusarium graminearum in Arabidopsis thaliana - Smith, Henry (2025)
Fusarium head blight (FHB) causes major crop loss to small grain cereal worldwide. Attempts to breed FHB resistant cultivars have so far been unsuccessful. Expected climatic changes are expected to increase FHB severity paving the way for research into what causes susceptibility. Research has found arthropod activity leads to increased FHB incidence. Here we test Fusarium graminearum resistance both with and without arthropod activity. Knock-out mutants were used to examine the resistance of specific genes found within the plant defence pathway. A total of 22 genes were presented by a Multi-Omnics Factor Analysis (MOFA) in relation to causing increased FHB susceptibility. We used the pathogen Fusarium graminearum to test resistance of Arabidopsis thaliana plants as well as undertaking gene expression analysis of wheat plants subject to both aphid and Fusarium graminearum treatments. In Arabidopsis Fusarium graminearum susceptibility was increased due to aphid infestation. The use of mutants enabled specific genes to be associated with either susceptibility of resistance as well as confirming plant hormone signalling pathways. We propose a new interaction between genes found in jasmonic acid signalling (ORA59) and ethylene signalling pathways (ORE1). Further work is required to confirm this pathway including the use of mutants of these two genes.